2008
DOI: 10.4141/cjss06030
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two process-based models to estimate soil N2O emissions in Eastern Canada

Abstract: . 2008. Evaluation of two process-based models to estimate soil N 2 O emissions in Eastern Canada. Can. J. Soil Sci. 88: 251Á260. Process-based models play an important role in the estimation of soil N 2 O emissions from regions with contrasting soil and climatic conditions. A study was performed to evaluate the ability of two process-based models, DAYCENT and DNDC, to estimate N 2 O emissions, soil nitrate-and ammonium-N levels, as well as soil temperature and water content. The measurement sites included a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(49 citation statements)
references
References 11 publications
5
41
3
Order By: Relevance
“…We could expect that the increasing temperatures in future climate accelerate the decomposition of the soil organic carbon as expected by Smith et al (2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We could expect that the increasing temperatures in future climate accelerate the decomposition of the soil organic carbon as expected by Smith et al (2008).…”
Section: Resultsmentioning
confidence: 99%
“…DNDC (Denitrification-Decomposition) model demonstrated a distinguished capacity of predicting trace gas emissions and soil organic carbon dynamics in agro-ecosystems (Li et al 1992;Li 2000). The original purpose of developing the DNDC model was to quantify the impacts of climate change and management on greenhouse gas emissions from agricultural lands in the U.S. During the past decade, DNDC has been tested by many researchers worldwide with promising results (Brown 1995;Smith et al 1997;Jagadeesh Babu et al 2006;Smith et al 2008). DNDC model is utilized first of all for evaluation of nitrous oxide in conditions of Slovakia on regional scale Šiška & Horák 2007).…”
Section: Agriculture (Poľnohospodárstvo) 57 2011 (3): 85−95mentioning
confidence: 99%
“…Higher soil N 2 O emissions have been reported from soils that received livestock manure than from those that received synthetic fertiliser. Smith et al (2008) reported 0.23 kg/ha of N 2 O emissions for a maize field that received synthetic fertiliser (150 kg/ha) and 1.21 and 3.1 kg/ha for the field that received pig slurry at the rates of 60 and 120 t/ha, respectively. Therefore, the higher GHG-intensity estimates for split and single scenarios in our study could be associated with the use of hog manure on grassland causing increased soil N 2 O emissions.…”
Section: Evaluation Of the Addition Of Hog Manurementioning
confidence: 99%
“…2, Table 5). Several local-and global-scale studies have compared DNDC and DAYCENT models and observed differences in estimated N loss (Del Grosso et al 2006Grosso et al , 2009Smith et al 2008;Abdalla et al 2010). Furthermore, on a farm-component scale, inconsistencies have been reported in field studies designed to measure the impact of timing and amount of manure application on GHG emissions.…”
Section: Evaluation Of the Addition Of Hog Manurementioning
confidence: 99%
“…In a study conducted by Brilli et al (2017), a literature review of the sources of error in different modelling studies was conducted. Based on values reported by different modelling studies, one of the most common causes in uncertainty in modelled N 2 O emissions from DDC, and also from other models, was uncertainty or incorrectly simulated water filled pore space (WFPS) by the model tended to by the underlying cause of discrepancies between experimental and modelled datasets (Abdalla et al, 2010;Xing et al, 2011;Gabrielle et al, 2006 andSmith et al, 2008). The implementation of management practices by DDC is also a source of error in modelled estimates.…”
Section: Region A) Grasslandsmentioning
confidence: 99%